2012
DOI: 10.4269/ajtmh.2012.11-0090
|View full text |Cite
|
Sign up to set email alerts
|

Towards Universal Coverage: Examining Costs of Illness, Payment, and Coping Strategies to Different Population Groups in Southeast Nigeria

Abstract: Abstract. This study investigated the costs of illness to households in different socio-economic status (SES) groups and geographic places of abode in addition to the mechanisms that the different population groups used to pay for health services and cope with payments. A cross-sectional descriptive study of 3,200 households selected from six communities in two states was conducted using interviewer-administered pre-tested questionnaires. An SES index was used to divide the households into quartiles, and χ 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 21 publications
0
47
0
Order By: Relevance
“…It could also disrupt children education. 1,31,32 The consequence can be enormous with poor health outcome, poverty, and sometimes death. Most of these are avoidable where there is a well-functioning prepayment scheme for health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It could also disrupt children education. 1,31,32 The consequence can be enormous with poor health outcome, poverty, and sometimes death. Most of these are avoidable where there is a well-functioning prepayment scheme for health.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with findings in some previous studies. 1,24 Earlier works, 34,44 have made useful suggestions about technical design of health insurance such as frequency and amount of contribution that will suit different socioeconomic groups of people. Also innovative ways of fund-raising at the domestic level especially on goods purchased and services sought by the better -off in the society as a source of revenue collection to help the poor and the needy for a sustainable health-care financing scheme have been suggested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We know relatively little about the strategies that households adopt to cope -or, at least, try to cope -with the financial costs of illness, and we have few data to show how such coping strategies affect the future welfare of the households that implement them. 10 In the few relevant studies that have been conducted, the coping strategies that are followed have been found to differ with the type of disease involved, 6,7,[11][12][13] with the sector (private or public) providing the outpatient facilities used, if any, 9,14 with the need for inpatient care, [14][15][16] and with the economic status of the patients or their households. 9,10,14,17 In Bangladesh, a country with high burdens of both noncommunicable and infectious diseases, out-of-pocket payments remain the most important source of funding for health care.…”
Section: Introductionmentioning
confidence: 99%